2018
DOI: 10.1093/hropen/hoy014
|View full text |Cite
|
Sign up to set email alerts
|

Intention of having a second child among infertile and fertile women attending outpatient gynecology clinics in three major cities in China: a cross-sectional study

Abstract: STUDY QUESTION What is the intention to have a second child among women attending outpatient gynecology clinics in three major cities in China? SUMMARY ANSWER In total, 69.3% of the participants expressed the intention to have a second child and this was related to infertility status, pronatalist attitudes, and sociodemographic factors. WHAT IS KNOWN ALREADY In 2016, the new universal two-child policy was introduced in China enabling all Chin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 39 publications
(44 reference statements)
0
11
0
Order By: Relevance
“…1 As a systemic problem, fertility intentions are influenced by many factors including the economy, fertility policies, level of education, the environment, and public services. 2 Despite the implementation of the two-child policy in 2015, the total number of annual births in China has not shown a clear trend of growth. According to the China Health Statistics Yearbooks of 2018 and 2019, the number of live births by pregnant women in China dropped from 18.47 million in 2016 to 17.58 million in 2017, and then fell to 13.62 million in 2018.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 As a systemic problem, fertility intentions are influenced by many factors including the economy, fertility policies, level of education, the environment, and public services. 2 Despite the implementation of the two-child policy in 2015, the total number of annual births in China has not shown a clear trend of growth. According to the China Health Statistics Yearbooks of 2018 and 2019, the number of live births by pregnant women in China dropped from 18.47 million in 2016 to 17.58 million in 2017, and then fell to 13.62 million in 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Fertility intention is the expression of fertility desire based on an individual or family preference for children, taking into account various limitations such as the ideal number of children, gender, time, and interval of pregnancy 1 . As a systemic problem, fertility intentions are influenced by many factors including the economy, fertility policies, level of education, the environment, and public services 2 …”
Section: Introductionmentioning
confidence: 99%
“…However, only 1.45 million (13.2%) of the 11 million eligible couples applied for permission to have a second child by May 2015 1 4. Fertility intent is regarded as a predictor of fertility behaviour;5 and in addition to policy, intent to procreate is also influenced by individual, social, economic and cultural factors 4 6. Several investigators have reported on the intent to have a second child in China (which varies from 13.2% to 69.3%) and its associated factors, including age, occupation, educational level, and gender of the first child 4–8.…”
Section: Introductionmentioning
confidence: 99%
“…Fertility intent is regarded as a predictor of fertility behaviour;5 and in addition to policy, intent to procreate is also influenced by individual, social, economic and cultural factors 4 6. Several investigators have reported on the intent to have a second child in China (which varies from 13.2% to 69.3%) and its associated factors, including age, occupation, educational level, and gender of the first child 4–8. However, these studies were principally conducted in particular populations or settings, such as a rural population, women attending outpatient gynaecology clinics, or women from one specific province.…”
Section: Introductionmentioning
confidence: 99%
“…Second, women’s fertility is strongly linked to age. Women aged 35 years or older have significant uncertainty in their diminished reproductive potential,26 and may be more sensitive to the narrowing chance of childbearing. According to the theory of planned behaviour, a positive belief and attitude toward one thing would promote the intention to take action 27.…”
Section: Discussionmentioning
confidence: 99%